Neige et Citrouille: Marché Atwater and Seasonality - Newman, Lenore (Cuizine)

(untitled) (McGill University Library, 2012)
After a long period of decline, urban farmers’ markets are playing a revitalized role in food distribution in North America as interest in local food increases. Such markets can reveal underlying geographies of cuisine and culture in the surrounding neighbourhoods. Marché Atwater in Montreal, Quebec, was observed over several years in different seasons to study how the space interacted with the surrounding community. Marché Atwater was found to reflect and influence the sense of seasonality in the surrounding neighbourhood of Saint-Henri. The space served as a critical gathering point in a changing urban area and acted as a point of distribution for interesting food practices. A Pecha Kucha photographic presentation is presented to capture elements of the market throughout the year; and Pecha Kucha as a geographic technique is also explored.